Identification of genetic causes of congenital neurodevelopmental disorders using genome wide molecular technologies - Eglė Preikšaitienė; Laima Ambrozaitytė; Živilė Maldžienė; Aušra Morkūnienė; Loreta Cimbalistienė; Tautvydas Rančelis; Algirdas Utkus; Vaidutis Kučinskas (Acta Medica Lituanica, 2016)
Background. Intellectual disability affects about 1–2% of the general population worldwide, and this is the leading socio-economic problem of health care. The evaluation of the genetic causes of intellectual disability is challenging because these conditions are genetically heterogeneous with many different genetic alterations resulting in clinically indistinguishable phenotypes. Genome wide molecular technologies are effective in a research setting for establishing the new genetic basis of a disease. We describe the first Lithuanian experience in genome-wide CNV detection and whole exome sequencing, presenting the results obtained in the research project UNIGENE.